A novel role for α-tocopherol transfer protein (α-TTP) in protecting against chloroquine toxicity - Shichiri, Mototada; Rotzoll, Daisy E. (The journal of biological chemistry, 2012)
Chloroquine (CQ) is a widely prescribed anti-malarial agent and is also prescribed to treat autoimmune diseases. Clinical treatment with CQ is often accompanied by serious side effects such as hepatitis and retinopathy. As a weak base, CQ accumulates in intracellular acidic organelles, raises the pH, and induces osmotic swelling and permeabilization of acidic organelles, which account for CQ-induced cytotoxicity. We reported previously that CQ treatment caused α-tocopherol transfer protein (α-TTP), a gene product of familial vitamin E deficiency, to change its location from the cytosol to the surface of acidic organelles. Here we show that α-TTP plays a novel role in protecting against CQ toxicity both in vitro and in vivo. In the presence of CQ, rat hepatoma McARH7777 cells, which do not express α-TTP endogenously, showed more severe cytotoxicity, such as larger vacuolation of acidic organelles and caspase activation, than α-TTP transfectant cells. Similarly, α-TTP knockout mice showed more severe CQ toxicity, such as hepatotoxicity and retinopathy, than wild-type mice. These effects were not ameliorated by vitamin E supplementation. In contrast to bafilomycin A1 treatment, which prevents CQ accumulation in cells by raising the pH of acidic organelles, α-TTP expression prevented CQ accumulation without affecting the pH of acidic organelles. Taken together, our data suggest that α-TTP protects against CQ toxicity by preventing CQ accumulation in acidic organelles through a mechanism distinct from vitamin E transport.